Implementasi Konseling Multikultural dalam Menangani Masalah Body Shaming dan Diskriminasi Fisik Remaja - Jamila Sombo; Selvi Selvi; Retna Kurniazih; Maibo Saludung Patandung; Ronaldo Stefanus (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Body shaming and physical discrimination are significant issues affecting adolescents' psychological development. Adolescents who experience negative treatment related to their physical appearance often face low self-esteem, stress, and social isolation. This article discusses the implementation of multicultural counseling as an effective intervention strategy to address these problems. Multicultural counseling emphasizes understanding cultural differences, values, and social norms that influence perceptions of the body and appearance. This approach involves self-reflection techniques, group discussions, role-playing, and personal experience narratives to enhance self-awareness, empathy, and adolescents’ ability to cope with body shaming and physical discrimination. In addition, counselors provide education on social stereotypes, beauty standards, and the importance of inclusion, helping adolescents develop adaptive coping mechanisms. Research findings indicate that multicultural counseling can reduce negative psychological impacts, increase self-acceptance, and promote tolerance toward physical diversity. The implementation of this counseling is essential for creating social environments that support adolescents’ mental and emotional development. This article offers practical contributions for counselors, educators, and psychology practitioners in designing multicultural-based interventions that are sensitive to issues of body shaming and physical discrimination